Impact of systemic and tumor lipid metabolism on everolimus efficacy in advanced pancreatic neuroendocrine tumors (pNETs). Issue 7 (7th January 2019) - Vernieri, Claudio; Pusceddu, Sara; Fucà, Giovanni; Indelicato, Pietro; Centonze, Giovanni; Castagnoli, Lorenzo; Ferrari, Elisa; Ajazi, Arta; Pupa, Serenella; Casola, Stefano; Foiani, Marco; Mazzaferro, Vincenzo; et al.
Abstract : The mTOR inhibitor everolimus is effective against advanced pancreatic neuroendocrine tumors (pNETs). However, it can cause metabolic adverse events, such as hyperglycemia, hypertriglyceridemia and hypercholesterolemia. In this work we aimed at evaluating the impact of systemic and tumor lipid metabolism on everolimus efficacy. We carried out a monocentric, retrospective study to correlate plasma triglyceride and cholesterol levels with the progression free survival (PFS) of advanced pNET patients treated with everolimus. In formalin fixed, paraffin embedded (FFPE) tumor specimens, we also assessed by mRNA quantification and immunohistochemistry the expression of acetyl‐CoA carboxylase 1 (ACC1) and fatty acid synthase (FASN), two enzymes crucially involved in fatty acid biosynthesis, and we analyzed their impact on PFS. We evaluated 58 consecutive pNET patients who started everolimus between December 2006 and January 2015. Patients with higher plasma triglycerides during the first 3 months of treatment had an increased risk of disease progression (aHR 3.08, 95% CIs 1.15–8.21; p = 0.025). In 23 FFPE tumor specimens amenable for IHC evaluations, we found a positive correlation between ACC1 and FASN at both mRNA ( r = 0.87, p = 0.00045) and protein ( r = 0.68, p = 0.0004) level. Patients with higher ACC1 protein expression in metastatic lesions had significantly lower PFS when compared to patients with lower ACC1 levels (5.5 vs . 36 months; aHR 4.49, 95% CIs 1.08–18.72; p = 0.039). In conclusion, systemic and tumor lipid metabolism are associated with the PFS of everolimus‐treated patients with advanced pNETs; based on these findings, dietary and pharmacological interventions targeting lipid metabolism could improve everolimus efficacy in this patient population. Abstract : What's new? Pancreatic neuroendocrine tumors (pNETs) are highly heterogeneous, so to improve treatment, it's critical to learn more about how different tumor types respond to therapy. The mTOR inhibitor everolimus is a standard therapy for pNETs. Here, the authors conducted a retrospective study to evaluate how circulating triglyceride and cholesterol levels affect the efficacy of everolimus. Patients with higher plasma triglyceride levels at the start of treatment, they found, had worse outcomes. In addition, they noted a correlation between disease progression and higher intratumoral levels of ACC1, a key enzyme in fatty acid biosynthesis.